HIGH-RESOLUTION TOPOGRAPHY OF MERCURY FROM MESSENGER ORBITAL STEREO IMAGING – THE SOUTHERN HEMISPHERE QUADRANGLES - F. Preusker; J. Oberst; J. Oberst; A. Stark; S. Burmeister (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2018)
We produce high-resolution (222 m/grid element) Digital Terrain Models (DTMs) for Mercury using stereo images from the MESSENGER orbital mission. We have developed a scheme to process large numbers, typically more than 6000, images by photogrammetric techniques, which include, multiple image matching, pyramid strategy, and bundle block adjustments. In this paper, we present models for map quadrangles of the southern hemisphere H11, H12, H13, and H14.